Large-Scale Analysis of Combining Ability and Heterosis for Development of Hybrid Maize Breeding Strategies Using Diverse Germplasm Resources - Yu, Kanchao; Wang, Hui; Liu, Xiaogang; Xu, Cheng; Li, Zhiwei; Xu, Xiaojie; Liu, Jiacheng; Wang, Zhenhua; Xu, Yunbi (Frontiers in Plant Science, 2020)
Understanding and analysis of combining ability and heterosis among diverse maize germplasm are important for breeding hybrid maize (Zea mays L.). Using 28 temperate and 23 tropical maize inbreds that represent different ecotypes and worldwide diversity of maize germplasm, we first developed a large-scale multiple-hybrid population (MHP) with 724 hybrids, which could be divided into three subsets, 325 temperate diallel hybrids and 136 tropical diallel hybrids generated in Griffing IV, and 263 temperate by tropical hybrids generated in NCD II. All the parental lines and hybrids were evaluated for 11 traits in replicated tests across two locations and three years. Several widely used inbreds showed strong general combing ability (GCA), and their derived hybrids showed strong specific combining ability (SCA). Heterosis is a quantiﬁable, trait-dependent and environment-speciﬁc phenotype, and the response of parental lines and their hybrids to environments resulted in various levels of heterosis. For all the tested traits except plant height and hundred grain weight, NCD II (temperate x tropical) hybrids showed higher average heterosis than the temperate and tropical diallel hybrids. Grain number per row and grain number per ear were two most important traits that determined yield heterosis. The hybrids from heterotic groups, Reid x SPT, Reid x LRC, SPT x PA and Lancaster x LRC, contributed highly significantly positive SCA effects and strong heterosis for yield-related traits. Heterosis was more significantly and positively correlated with SCA than GCA, indicating that SCA can be used in heterosis prediction. The results reported in the present study not only contribute to developing breeding strategies, but also improve targeted breeding efficiency by using both temperate and tropical maize to broaden genetic basis. Large sets of parental lines with available genotypic information can be shared and used in worldwide hybrid breeding programs through open-source breeding strategy. Potential applications of the reported results in developing hybrid maize breeding strategies were also discussed.